Efficacy and safety of hydroxychloroquine for treatment of mild SARS‐CoV‐2 infection and prevention of COVID‐19 severity in pregnant and postpartum women: A randomized, double‐blind, placebo‐controlled trial - Raquel González; Anna Goncé; Mª. del Mar Gil; Edurne Mazarico; Elena Ferriols‐Pérez; Paloma Toro; Elisa Llurba; Elisa Saéz; Miguel Ángel Rodríguez‐Zambrano; Laura García‐Otero; Marta López; Belén Santacruz; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Pregnant women have an increased risk of severe COVID‐19. Evaluation of drugs with a safety reproductive toxicity profile is a priority. At the beginning of the pandemic, hydroxychloroquine (HCQ) was recommended for COVID‐19 treatment. Material and methods A randomized, double‐blind, placebo‐controlled clinical trial was conducted in eight teaching hospitals in Spain to evaluate the safety and efficacy of HCQ in reducing viral shedding and preventing COVID‐19 progression. Pregnant and postpartum women with a positive SARS‐CoV‐2 PCR (with or without mild COVID‐19 signs/symptoms) and a normal electrocardiogram were randomized to receive either HCQ orally (400 mg/day for 3 days and 200 mg/day for 11 days) or placebo. PCR and electrocardiogram were repeated at day 21 after treatment start. Enrollment was stopped before reaching the target sample due to low recruitment rate. Trial registration EudraCT #: 2020‐001587‐29, on April 2, 2020. Clinical trials.gov # NCT04410562, registered on June 1, 2020. Results A total of 116 women (75 pregnant and 41 post‐partum) were enrolled from May 2020 to June 2021. The proportion of women with a positive SARS‐CoV‐2 PCR at day 21 was lower in the HCQ group (21.8%, 12/55) than in the placebo group (31.6%, 18/57), although the difference was not statistically significant (P = 0.499). No differences were observed in COVID‐19 progression, adverse events, median change in QTc, hospital admissions, preeclampsia or poor pregnancy and perinatal outcomes between groups. Conclusions HCQ was found to be safe in pregnant and postpartum women with asymptomatic or mild SARS‐CoV‐2 infection. Although the prevalence of infection was decreased in the HCQ group, the statistical power was insufficient to confirm the potential beneficial effect of HCQ for COVID‐19 treatment.